Analisis Semiotika Tagline “Beli Semua Di Shopee” Dalam Membentuk Branding Shopee - Farid Mubarok; Siti Muyasaroh (4, 2025)
Based on the increasing competition in the e-commerce industry in Indonesia, taglines play a crucial role as verbal communication elements in shaping brand image. The tagline